2017
DOI: 10.1021/acssensors.6b00834
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biosensing: Progress and Perspectives

Abstract: In vivo biosensors are emerging as powerful tools in biomedical research and diagnostic medicine. Distinct from “labels” or “imaging”, in vivo biosensors are designed for continuous and long-term monitoring of target analytes in real biological systems and should be selective, sensitive, reversible and biocompatible. Due to the challenges associated with meeting all of the analytical requirements, we found relatively few reports of research groups demonstrating devices that meet the strict definition in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 90 publications
0
124
0
Order By: Relevance
“…Expanded studies on dissolution kinetics of semiconductors for transient electronics were reported by Kang et al [31] The authors correlated the dissolution rates of 100 nm thick NMs of polycrystalline silicon (p-Si), amorphous silicon (a-Si), silicon-germanium alloy (SiGe), and germanium (Ge) in aqueous solutions with different pH (7)(8)(9)(10) and temperature (room temperature and 37 °C) values. Equation (2)…”
Section: Inorganic Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanded studies on dissolution kinetics of semiconductors for transient electronics were reported by Kang et al [31] The authors correlated the dissolution rates of 100 nm thick NMs of polycrystalline silicon (p-Si), amorphous silicon (a-Si), silicon-germanium alloy (SiGe), and germanium (Ge) in aqueous solutions with different pH (7)(8)(9)(10) and temperature (room temperature and 37 °C) values. Equation (2)…”
Section: Inorganic Semiconductorsmentioning
confidence: 99%
“…Besides, the continuous diffusion of noninvasive and minimally invasive sensor systems for personalized medicine and sport&wellness activities envisages an ever‐growing electronic waste that poses serious environmental hazards, given the pervasive presence and rapid turn‐over of electronic devices in everyday life . The development of biodegradable electronic components and systems that facilitate disposal by natural dissolution in ambient or mild conditions without environmental threats could mitigate electronic waste problems …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, well-defined plasmonic substrates can also be prepared, typically through deposition on solid supports, [56,57] leading to maximized SERS signals, as well as uniform SERS enhancement factors across the entire surface, owing to their homogenous structure, so that the reproducibility of SERS analysis is greatly improved. [59,60] We present below some examples of supported SERS substrates that have been applied to the detection of monosaccharides. [59,60] We present below some examples of supported SERS substrates that have been applied to the detection of monosaccharides.…”
Section: Detection Of Saccharidesmentioning
confidence: 99%
“…[58] Such solid plasmonic substrates have been proposed for the long-term monitoring of target analytes in real biological systems. [59,60] We present below some examples of supported SERS substrates that have been applied to the detection of monosaccharides.…”
Section: Detection Of Saccharidesmentioning
confidence: 99%
“…[3,4,8,9] Herein, af luorideselective optode based on Al III octaethylporphyrin (Al[OEP]) as the ionophore [9] is employed to demonstrate the new paperbased ISO concept. [3,4,8,9] Herein, af luorideselective optode based on Al III octaethylporphyrin (Al[OEP]) as the ionophore [9] is employed to demonstrate the new paperbased ISO concept.…”
mentioning
confidence: 99%